The Occurrence of Noun Post-modifiers in Political News: A Corpus-based Study - Ari Murad Mohammed Salih; Hozan Hamid Ibrahim; Salih Ibrahim Ahmed (International Journal of Social Sciences & Educational Studies)
This research aims to investigate and observe the occurrences of noun post-modifiers in three English news websites, namely BBC News, CNN and Al Jazeera English by selecting five news articles from each to discover the frequency of noun post-modifier occurrences. The paper is carried out in the realm of corpus linguistics which approaches the study of naturally occurring language through the use of corpora which are collections of authentic texts. The type of the corpus adopted in the study is the observed corpus. Fifteen news articles have been selected from the three English websites so as to make a corpus to be the basis of the data analysis. Then the articles are read and analyzed depending on using a researchers-made template to meet the specific needs in the data collection process to find out the frequency of the occurrences of noun post-modifiers and their types. A quantitative method is adopted in doing the research. The research tries, on corpus-based evidence, to find out the most frequent type of noun post-modifier in real written form of English language. The significance of the research can be seen in the framework of corpus linguistics and English syntax in that it originates from both fields, hence researchers in these two areas can take benefit from its findings. Depending on the results, the most remarkable finding of the paper is that prepositional phrases are the most frequently used post-modifiers in noun phrases. On this basis, the main conclusion of the paper is that prepositional phrases have the highest rate of occurrence among all the noun post-modifiers in political news.